2016
DOI: 10.1108/ribs-02-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Trust and economic performance

Abstract: Purpose Level of trust among the members is considered to be an important component that contributes towards the economic growth in an economy. The purpose of this paper is to examine the effect of trust level along with income per capita, human capital (education level), investment, labor force and political institutions on the economic performance. Design/methodology/approach In this research, panel data as well as cross-country analysis were applied on a sample of 64 countries from 1980 to 2014. Countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The result showed that interpersonal and interorganizational trust were correlated. This connection affected cooperation processes (Zaheer et al, 1998), assists in partnership forming, and diminishes transaction costs (Niazi & Hassan, 2016). From the transaction cost perspective, a company increased production throughout the partnership with the business partners, as the internal exchange cost surpasses the external exchange cost (Brigham & Houston, 2019).…”
Section: Structural Model Assessmentmentioning
confidence: 99%
“…The result showed that interpersonal and interorganizational trust were correlated. This connection affected cooperation processes (Zaheer et al, 1998), assists in partnership forming, and diminishes transaction costs (Niazi & Hassan, 2016). From the transaction cost perspective, a company increased production throughout the partnership with the business partners, as the internal exchange cost surpasses the external exchange cost (Brigham & Houston, 2019).…”
Section: Structural Model Assessmentmentioning
confidence: 99%
“…From a financial perspective and regarding small and medium-scale organizations in the technology sector, Lee and Kwon (2017) identified sales growth, current ratio and research and development intensity as key drivers of performance. Other drivers comprise human capital and investment (Niazi and Hassan, 2016), stakeholder management (Ewurum et al ., 2020; Neves et al ., 2023) and technical enhancement (Ferreira et al ., 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Largely, antecedents of female employee performance research indicate a synthesis of contextual micro- and macro-level drivers. Studies examining the organizational-level determinants of female employee performance have embraced several aspects like culture, teamwork, leadership and other conveniently available and pronounced facets (Çera and Kusaku, 2020; Niazi and Hassan, 2016). Of particular interest, however, is the accentuation of the gender inequality issue in several organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trust is not only important from organizational stance but also from economic point of view. Business that takes place internationally is also based on trust which eventually affects the economic performance of the country (Niazi & Hassan, 2016). A number of studies have been conducted to propose that trust is an essential component for understanding group and individual behavior (Hosmer, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%